2021
DOI: 10.48550/arxiv.2103.12570
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Simulations of state-of-the-art fermionic neural network wave functions with diffusion Monte Carlo

Max Wilson,
Nicholas Gao,
Filip Wudarski
et al.

Abstract: Recently developed neural network-based ab-initio solutions (Pfau et. al arxiv:1909.02487v2) for finding ground states of fermionic systems can generate state-of-the-art results on a broad class of systems. In this work, we improve the results for this Ansatz with Diffusion Monte Carlo. Additionally, we introduce several modifications to the network (Fermi Net) and optimization method (Kronecker Factored Approximate Curvature) that reduce the number of required resources while maintaining or improving the mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 28 publications
1
31
0
Order By: Relevance
“…The diagram is representative but not exact, it does not contain all operations, for an exact description see Section III. mance on molecular systems [2][3][4][24][25][26].…”
Section: Permutation Equivariant Layersmentioning
confidence: 99%
“…The diagram is representative but not exact, it does not contain all operations, for an exact description see Section III. mance on molecular systems [2][3][4][24][25][26].…”
Section: Permutation Equivariant Layersmentioning
confidence: 99%
“…Using a deep neural network-based ansatz for variational Monte Carlo (VMC) has recently emerged as a novel approach for highly accurate ab-initio solutions to the multi-electron Schrödinger equation [1][2][3][4][5]. It has been observed that such methods can exceed gold-standard quantum-chemistry methods like CCSD(T) [6] in accuracy, with a computational cost per step scaling only with O(N 4 ) in the number of electrons [4].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning a variety of related works to put the present contribution into a broader perspective. First, there have been various wavefunction ansatzes for ground-state VMC calculation of fermions, from the traditional Slater-Jastrow [19], backflow [20][21][22][23] to more recent attempts based on neural networks [24][25][26][27][28][29][30][31]. However, unitary transformations are not considered in these ansatzes, since only a single wavefunction, instead of a whole basis, is needed in this situation.…”
Section: Introductionmentioning
confidence: 99%